PEMBINAAN KESADARAN LINGKUNGAN HIDUP DI PONDOK PESANTREN: STUDI KASUS DI PONDOK PESANTREN AL-MANSUR DARUNNAJAH 3 KABUPATEN SERANG - Ali Muhtarom (IBDA` : Jurnal Kajian Islam dan Budaya, 2014)
This paper discusses the Islamic boarding school respond toward environmental problem and the implementation of Islamic values in environmental awareness development in Al-Mansur Darunnajah 3 Kabupaten Serang, Banten Islamic boarding school. There are three efforts; first, there is an enthusiasm on doing the religious teaching; second, proactive on doing the cleaning; and third, the school concern on developing the eco-Islamic boarding school. There are three kinds of Islamic values implementation; first, intrinstic concern on practising Islamic values; second, creating slogans about prohibition on any kind of environmental damage and throwing rubish, and popularize the motto â€œbersih, indah, dan amanâ€. The third, there are special rules conducting the environmental problems by giving punishment and organize the schedule for cleaning.